2013
DOI: 10.2135/cropsci2012.02.0112
|View full text |Cite
|
Sign up to set email alerts
|

Genomewide Selection versus Marker‐assisted Recurrent Selection to Improve Grain Yield and Stover‐quality Traits for Cellulosic Ethanol in Maize

Abstract: M arker-assisted selection for quantitative traits has traditionally relied on fi rst identifying markers linked to quantitative trait loci (QTL). A specifi c form of marker-assisted selection in maize (Zea mays L.) is marker-assisted recurrent selection (MARS) in which (i) one generation of phenotypic selection in the target environment is conducted, (ii) markers with signifi cant eff ects are used to predict the performance of individual plants, and (iii) several generations of marker-only selection are perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
167
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(179 citation statements)
references
References 32 publications
8
167
2
2
Order By: Relevance
“…In general, these studies showed good prediction accuracies for GY and other traits evaluated by means of several random cross-validation partitions of the data. The first public study confirming these previous findings on genomicenabled prediction was that of Massman et al (2013), who showed that genomic selection improved genetic gains per unit of time in one biparental temperate maize (Zea mays L.) population. Recently, Beyene et al (2015) achieved important genetic gains in GY through genomic selection in eight tropical biparental CIMMYT maize populations; these authors evaluated cycles of genomic selection in severe drought environments in sub-Saharan Africa.…”
Section: Introductionsupporting
confidence: 54%
“…In general, these studies showed good prediction accuracies for GY and other traits evaluated by means of several random cross-validation partitions of the data. The first public study confirming these previous findings on genomicenabled prediction was that of Massman et al (2013), who showed that genomic selection improved genetic gains per unit of time in one biparental temperate maize (Zea mays L.) population. Recently, Beyene et al (2015) achieved important genetic gains in GY through genomic selection in eight tropical biparental CIMMYT maize populations; these authors evaluated cycles of genomic selection in severe drought environments in sub-Saharan Africa.…”
Section: Introductionsupporting
confidence: 54%
“…The estimated marker effects are then applied to predict the breeding value of nonphenotyped individuals based on their molecular marker profiles. The great potential of genomic selection for complex traits has been demonstrated in several experimental studies in plant and animal breeding populations (Bernardo, 2008;Heffner et al, 2009;Heslot et al, 2012;Massman et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The GS theoretical framework developed over a decade ago (Meuwissen et al 2001) is now enabled by efficiency gains in DNA marker (Davey et al 2011;Elshire et al 2011;Poland and Rife 2012) and, more recently, plant phenotypic (White and Conley 2013) data generation, management and analysis; and offers proven value in economic plant species (Massman et al 2013;Spindel et al 2015).…”
Section: Genomic Selectionmentioning
confidence: 99%
“…This includes empirical and modelled evidence to assess comparative efficiencies per unit resource (Massman et al 2013;Resende et al 2013) across the range of traits under selection.…”
Section: Genomic Selectionmentioning
confidence: 99%